Discourse Analysis of Pakistani Media Coverage During “Aurat March” 2022: A Feminist Approach - Aniqa Tabassum; Ahmad Farid; Hafsa Akhtar (Universitas Syiah Kuala, 2023)
The purpose of this study is to investigate and examine the image and representation of women in the Pakistani media, focusing on prejudice, portrayal, and their roles within society. Despite the emergence of modern feminism and social progress, Pakistani women continue to face oppression. Recognizing the influential power of the media, this research aims to examine its potential to bring about social change when approached with sincerity, as it possesses the ability to shape public opinions and attitudes. To accomplish this, a qualitative research approach has been adopted. The study involves the collection and analysis of data from specific talk shows aired on various news channels within the Pakistani media landscape. By focusing on these talk shows, the research seeks to explore the media's role in presenting and discussing key aspects of the Aurat March, a women's rights movement in Pakistan. The results show that the problem arises from the misunderstood discourse related to the movement. Oftentimes, it was related to culturally insensitive content about aurat march by media covering the other side of the slogan which further fueled the controversial religious rhetoric of the nation. This fenomenon implies that media platforms can either perpetuate or challenge prevailing prejudices and stereotypes.